Kidney Infarction in Patients With COVID-19 (2020)
Coronavirus disease 2019 (COVID-19) is a contagious life-threatening infection caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Recent findings indicate an increased risk for acute kidney injury during COVID-19 infection. The pathophysiologic mechanisms leading to acute kidney injury in COVID-19 infection are unclear but may include direct cytopathic effects of the virus on kidney tubular and endothelial cells, indirect damage caused by virus-induced cytokine release, and kidney hypoperfusion due to a restrictive fluid strategy. In this report of 2 cases, we propose an additional pathophysiologic mechanism. We describe 2 cases in which patients with COVID-19 infection developed a decrease in kidney function due to kidney infarction. These patients did not have atrial fibrillation. One of these patients was treated with therapeutic doses of low-molecular-weight heparin, after which no further deterioration in kidney function was observed. Our findings implicate that the differential diagnosis of acute kidney injury in COVID-19–infected patients should include kidney infarction, which may have important preventive and therapeutic implications.